Identification of genomic regions related to age at first calving and first calving interval in water buffalo using single-step GBLUP - Araujo Neto, Francisco Ribeiro de; Takada, Luciana [UNESP]; Santos, Daniel Jordan Abreu dos; Aspilcueta-Borquis, Rusbel Raul; Cardoso, Diercles Francisco [UNESP]; Nascimento, Andre Vieira do [UNESP]; Leao, Karen Martins; Oliveira, Henrique Nunes de [UNESP]; Tonhati, Humberto [UNESP] (Wiley-Blackwell, 2020)
In Brazil, water buffaloes have been used to produce milk for mozzarella cheese production. Consequently, the main selection criterion applied for the buffalo genetic improvement is the estimated mozzarella yield as a function of milk, fat and protein production. However, given the importance of reproductive traits in production systems, this study aimed to use techniques for identifying genomic regions that affect the age at first calving (AFC) and first calving interval (FCI) in buffalo cows and to select candidate genes for the identification of QTL and gene expression studies. The single-step GBLUP method was used for the identification of genomic regions. Windows of 1 Mb containing single-nucleotide polymorphisms were constructed and the 10 windows that explained the greatest proportion of genetic variance were considered candidate regions for each trait. Genes present into the selected windows were identified using the UOA_WB_1 assembly as the reference, and their ontology was defined with the Panther tool. Candidate regions for both traits were identified on BBU 3, 12, 21 and 22; for AFC, candidates were detected on BBU 6, 7, 8, 9 and 15 and for first calving interval on BBU 4, 14 and 19. This study identified regions with great contribution to the additive genetic variance of age at first calving and first calving interval in the population of buffalo cows studied. The ROCK2, PMVK, ADCY2, MAP2K6, BMP10 and GFPT1 genes are main candidates for reproductive traits in water dairy buffaloes, and these results may have future applications in animal breeding programs or in gene expression studies of the species.
Keywords: Bubalus bubalis; puberty; reproduction